Isolations and purification of carcinoembryonic antigen from colorectal carcinomas - Rabel, Bandula (Faculty of Medicine, University of Colombo, 1987)
Isolation and purification of carcinoembryonic antigen from fetal digestive tissues and tumors of stomach, colon and recturm by a procedure which includes molecular exclusion chromatography on Sepharose 6B followed by Sephadex G-200 has been established for the first time in Sri Lanka. Considerable yeilds are obtained from this simple, rapid, inexpensive purification procedure of CEA.
A thesis submitted in partial fulfilments of the requirements the degree of science (biochemistry) the University of Colombo
Keywords: Carcinoembryonic Antigen; Carcinoembryonic Antigen-Isolation; COLORECTAL EOPLASMS